Woke up this morning ebook The definitive oral history of the sopranos. - Imperioli, Michael (2021)
INSTANT NEW YORK TIMES BESTSELLER "I will be reading and rereading Woke Up This Morning....These rollicking gabfests... bring together nearly everyone, on screen and off, who made the series a creative and cultural landmark. The freely offered admiration expressed by so many for their missing comrade and unofficial cast captain, Gandolfini, makes these stories about playing tough guys all the more tender." —New York Times "Essential for fans, with a revelation on every page." —Kirkus Reviews "A spectacular tell-all...the ultimate book on The Sopranos, made by the people who lived it." —Publishers Weekly Expanding on their hit Talking Sopranos podcast with exclusive interviews for the book with the cast, crew, producers, writers, directors and creators, stars Michael Imperioli and Steve Schirripa deliver the definitive oral history of the landmark television series and streaming hit The Sopranos. Packed with untold stories from behind the scenes and on the set, they're spilling all the secrets. Who made the phone call that got HBO to launch The Sopranos? What's the significance of all those eggs? And, what the hell ever happened to the Russian? Michael Imperioli, Steve Schirripa, and the entire cast and crew of The Sopranos have all the answers—and they're revealing where all the bodies are buried. Inspired by the incredibly successful Talking Sopranos podcast, The Sopranos stars Michael Imperioli (Christopher Moltisanti) and Steve Schirripa (Bobby Baccalieri) finally reveal all the Soprano family secrets in a surprising, funny, and honest new book. Woke Up This Morning is the definitive behind-the-scenes history of the groundbreaking HBO series that became a worldwide cultural phenomenon, ushered in a new Golden Age of Television, and to this day continues to be one of the most binged shows of all time. Michael and Steve tell all the incredible stories that The Sopranos fans have been waiting to hear for over twenty years. The book covers the entire history of The Sopranos series from the original concept pitch and casting to the infamous cut to black—and answer many of the thousands of fan questions sent to the podcast, as well as dispel some widely propagated myths and reveal things no one outside the show would even know to ask.